Preserving the Sixties Britain and the ‘Decade of Protest’ - Harris, Trevor; Castro, Monia O’Brien.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Re-examining the long-held belief that the Sixties in Britain were dominated mainly by 'youth' and 'protest', the authors in the collection argue that innovation was everywhere shadowed by conservatism. A decade fascinated by itself and, especially, by the future, it also was tormented by self-doubt and accompanied by a fear of losing the past.
Keywords: Great Britain-History.; Social history; Civilization-History.; World politics; History, Modern; History of Britain and Ireland; Social History; Cultural History; Political History; Cultural Studies; Modern History